Peranan Kurikulum Dalam Mencapai Tujuan Pendidikan - Mulia, Jumadil Ranto; Nasution, Bermawi; Asmendri, Asmendri; Sari, Milya (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
The curriculum in education plays a very large role in determining a country's educational progress, from concept to application and practice in the field. The method used in this research uses analysis of literature review data collection from journals, internet media and online news media. These results are also consistent with character education theory which emphasizes the importance of moral learning in developing better individuals. A curriculum that is more oriented towards developing competencies and skills can have a positive impact on students' educational outcomes, helping them become better prepared to enter the world of work or pursue higher education. Cultivating their interests and talents has a higher level of motivation in the learning process. A curriculum designed to foster students' critical and creative souls can have a positive impact in preparing them for the challenges that exist in the real world. A curriculum that is responsive to future developments can help students become better prepared to face future challenges. Therefore, developing and implementing an effective curriculum is one of the keys to the success of a quality and relevant education system.